Seasonal Chemical Variability of Aloysia polystachya Leaves - Retta, Daiana S.; Di Leo Lira, Paola Maria del Rosario; Balsamo, Maricel; Delpupo, Macarena; Moscatelli, Valeria A.; Dobrecky, Cecilia; Flor, Sabrina; Guariniello, Julian; Bandoni, Arnaldo Luis; van Baren, Catalina María (Springer, 2022)
The use of natural products as food ingredients requires adequate regulation and safety assessment for its legal commercialization. Aloysia polystachya (Griseb.) Moldenke, Verbenaceae, is a native plant from Argentina with aromatic and medicinal properties. A selected Argentinean genotype of this species was harvested and evaluated monthly for 1 year involving the different stages of a whole crop cycle to determine its chemical variability. The volatile and non-volatile fractions of its air-dried leaves were characterized. The content of total polyphenols, spectrophotometrically estimated by the Folin-Ciocalteu method, varied from 4.2 to 6.2% gallic acid equivalents. Verbascoside identification was confirmed by HPLC-MS/MS, and its content was evaluated by HPLC with a multiple wavelength detector, ranging from 2.2 to 5.4%. Volatile oil yield obtained by hydrodistillation was calculated in each sample, and their chemical compositions were determined by GC-FID-MS. The yield values ranged from 1.5 to 6.6% being rich in carvone (62.3–81.9%) and limonene (12–32.7%). The contents of verbascoside, polyphenols, and volatile oil fluctuated throughout the year. The most suitable profile was found from September to December. This work is a contribution to the standardization and quality control of A. polystachya to be used for food or medicinal purposes.